Understanding the origins of the ring‐necked parakeet in the UK. (11th December 2019) - Heald, O. J. N.; Fraticelli, C.; Cox, S. E.; Stevens, M. C. A.; Faulkner, S. C.; Blackburn, T. M.; Le Comber, S. C.
Abstract: The ring‐necked parakeet Psittacula krameri is one of the best‐known invasive species in the UK. It is also arguably the species whose origins as an invasive have been the subject of the greatest speculation, with explanations ranging from birds escaping from the set of the film ' The African Queen ' to animals being released in Carnaby Street in London by Jimi Hendrix in the 1960s. Here, we use geographic profiling – a statistical technique originally developed in criminology to prioritise the large lists of suspects typical in cases of serial crime such as murder, rape and arson, but more recently applied to ecology and conservation biology – to analyse the spatial patterns of the ring‐necked parakeet, from the first detailed records in the 1960s to the 21st century and ask whether spatial analysis supports these hypotheses. We show that, despite the undoubted appeal of the different hypotheses concerning their origin, spatial analysis provides no support for any of them, leading us to conclude that the birds' establishment in Britain is more likely to be a consequence of repeated releases and introductions, a view supported by a detailed search of the British Newspaper Archive. More generally, our study shows how geographic profiling can be used to understand the spatial patterns of biological invasions over time. Abstract : The origins of the ring‐necked parakeet, Psittacula krameri, in the UK are the subject of much speculation, with the most common explanations being birds released from the set of Humphrey Bogart's 'African Queen' or by the rock star Jimi Hendrix in Carnaby Street. Here, we show that spatial analysis provides no support for any of these theories. We further show from a systematic search of the British Newspaper Archive that the spread of the ring‐necked parakeet follows a series of sensationalist newspaper headlines about psittacosis in the 1950s and suggest that releases following this are a more likely cause of their establishment.